Play and practice in the development of sport‐specific creativity in team ball sports - Memmert, Daniel; Baker, Joseph; Bertsch, Claudia (High ability studies, 2010)
Current theoretical approaches regarding the development of creativity support the view that gathering diversified experience over years is an ideal medium for creative thinking. This study examined the role of practice conditions in the development of creative behavior in team ball sports. Twelve trainers selected the most creative and the least creative players from their teams. These athletes (n=72) provided information about the quantity and type of sport‐specific and other related practice activities undertaken throughout their careers. Results indicated significant differences between the groups for time spent in unstructured play activities and a marginally significant difference for total time spent in training for their main sport. In both cases, more creative players accumulated more time than their less creative counterparts.